Elaboración de un manual de buenas prácticas de manufactura (BPM), para la empresa deshidratadora de frutas Solram en el sector la Armenia, cantón Quito 2014 - Topón Chanataxi, Carlos Andrés (2015)
The Good Manufacturing Practices is a very important and constant work tool that applies in each and every one of the processes of food production, it the main tool to ensure safe food and safe to consume. This work was done in the fruit dried fruits SOLRAM company which is engaged in the production of dehydrated fruits where we evaluate the current situation that the company is considering the checklist that is based on the parameters established in the regulations No. 3253 GMP for processed foods which are issued by the Constitutional Court in 2002 in the then government of Dr. Gustavo Noboa Bejarano....